Ley orgánica de regulación y control de poder de mercado y su impacto en las prácticas comerciales del sector de bienes de consumo alimenticio en las cadenas de supermercados y proveedores de la ciudad de Chone - Buste Zambrano, Jorge Luis (2021)
This research was developed in order to analyze the Organic Law for the Regulation and Control of Market Power and its impact on the commercial practices of the food consumer goods sector in the supermarket chains and suppliers of the city of Chone. For its fulfillment, three documentary and descriptive methodological phases were carried out: in the first, the current state of commercial practices and its relationship with the Organic Law of Regulation and Control of Market power was established, for which it was required to design and validate the instruments evaluation with the Delphi method, from which interviews were applied to the support technician of the Superintendency of Control and Market Power and the supermarkets included in the investigation. Subsequently, compliance with Resolution 014 was determined, through a matrix of inspection evaluation criteria, and a survey of the suppliers of the supermarkets studied. Finally, the problems found were analyzed with an Ishikawa Diagram, to generate an improvement proposal using the 5w + 1h technique. The results establish that commercial practices are deficient in the food consumer goods sector of the Chone canton, which is why it is concluded that more training is required on the provisions of Resolution No. 014 and a commitment to comply with the parties involved.